Diagnostic usefulness of transtracheal aspiration in lower respiratory tract infections - Mohanty, Aroop; Kabi, Ankita; Mohanty, Ambika Prasad; Gupta, Pratima; Gupta, Priyanka (International Journal of Research in Medical Sciences, 2017)
Background: The incidence of pulmonary infections is on a constant rise. The present study was undertaken in order to identify those patients in whom transtracheal aspiration is most likely to provide information not obtainable from evaluation of expectorated sputum and delineates the clinical conditions under which transtracheal aspiration is indicated. Methods: A total of 50 patients of lower respiratory tract infections were studied. Both sputum and trans-tracheal aspirate samples were compared by Gram’s stain and culture methods. Results: Gram’s staining of the sputum was non-helpful in most cases as it showed mixed organisms while trans-tracheal aspiration showed only single type of colony. Culture showed less growth in sputum samples as compared to trans-tracheal aspirates. Conclusions: Trans-tracheal aspirate appears to be a very good method for isolating infective agents in lower respiratory tract infections. Besides by passing the contaminants of the oropharynx, it pinpoints the organism in most cases.